Preparative isolation and puriï¬cation of 12,13-dihydroxyeuparin from Radix Eupatorii Chinensis by high-speed counter-current chromatography - Mei Yang; Xin-Jun Xu; Chun-Yan Xie; Jie-Yun Huang; Zhi-Sheng Xie; De-Po Yang (Elsevier, 2012)
An efï¬cient method for the isolation and puriï¬cation of 12,13-dihydroxyeuparin from Radix Eupatorii Chinensis by high speed counter-current chromatography (HSCCC) was established in this paper. The ether extracts of Radix Eupatorii Chinensis were puriï¬ed by HSCCC with a solvent system of hexyl hydrideâethyl acetateâmethanolâwater (1:2:1:2, v/v/v/v). The upper phase was used as the stationary phase and the lower phase as the mobile phase. About 8.4Â mg of 12,13-dihydroxyeuparin was obtained from 200Â mg of ether extracts from Radix Eupatorii Chinensis in one-step HSCCC separation, with the purity of 96.71%, as determined by HPLC. After methanolâwater recrystallization, the purity of 12,13-dihydroxyeuparin reached 99.83%. Such a simple and effective method was fairly useful to prepare pure compound as reference substances for related study on Radix Eupatorii Chinensis. Keywords: Radix Eupatorii Chinensis, High speed counter-current chromatography (HSCCC), 12,13-dihydroxyeuparin